2021
DOI: 10.1049/mia2.12169
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal coupling impedance of a particle traveling in PEC rings: A regularised analysis

Abstract: The analysis of a charged particle traveling through one, two, or infinite conducting rings is presented. The problem is formulated in the spectral domain as integral equations of Fredholm type, solved by Galerkin's method employing entire domain functions factorising the correct edge behaviour of the unknown induced current. As a result, high accuracy and numerical stability are achieved. Numerical results are presented, proving the effectiveness of the method, and the parameters relevant to accelerator physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A first possibility is to subtract the asymptotic behavior of the kernels, thus leading to integrals of the product of four Bessel functions and powers. Such an approach has been used, for example, in [44] in a simpler, scalar case. As a matter of fact, it can be shown that the integral of the product of four Bessel functions can be analytically evaluated as a Meijer function.…”
Section: Mom Solution: Projectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first possibility is to subtract the asymptotic behavior of the kernels, thus leading to integrals of the product of four Bessel functions and powers. Such an approach has been used, for example, in [44] in a simpler, scalar case. As a matter of fact, it can be shown that the integral of the product of four Bessel functions can be analytically evaluated as a Meijer function.…”
Section: Mom Solution: Projectionmentioning
confidence: 99%
“…However, even more can be said: such an approach properly works, i.e., it is also possible to apply Fredholm theory when the matrix operator corresponding to the singular part is invertible (not necessarily diagonal) with a continuous two-side inverse and the residual part is a compact operator [26]. Such a procedure has been called Method of Analytical Preconditioning (MAP) [27], and has been used to solve a huge number of scattering, radiation, and propagation problems [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis provided in the paper ‘Longitudinal coupling impedance of a particle travelling in PEC rings: A regularised analysis’ by Assante et al. [16], of relevance in the accelerator and collider physics, is carried out in the Hankel transform domain. The obtained first‐kind singular integral equation is discretised by means of the method of analytical preconditioning with expansion functions reconstructing the behaviour of the unknowns at the edges.…”
Section: Articles′ Overviewmentioning
confidence: 99%
“…This is what happens when: (1) the Galerkin scheme is adopted, and (2) the selected expansion functions are orthonormal eigenfunctions of a suitable operator containing the most singular part of the integral operator at hand. Such an approach, appropriately called method of analytical preconditioning, is very effective, as clearly shown in the literature devoted to the study of the scattering, propagation, and radiation problems [23][24][25][26][27][28][29][30][31][32][33]. Another way to obtain a guaranteed-convergence consists in solving numerically the singular integral equation by means of a Nyström-type discretization scheme taking into account the singularity of the integral equation and the behavior of the unknowns at the edges [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%